2008
DOI: 10.1542/peds.2008-1183
|View full text |Cite
|
Sign up to set email alerts
|

Parental Alcohol Screening in Pediatric Practices

Abstract: A majority of parents would agree to being screened for alcohol problems in the pediatric office. Regardless of their alcohol screen status, parents are accepting of being screened by the pediatrician, a computer-based questionnaire, or a paper-and-pencil survey. Parents who screen positive prefer that the pediatrician discuss the problem further with them and present options for referral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…Office staff could be encouraged to report any of these signs or symptoms to the pediatrician. 67 Additional guidance on dealing with the judgmentimpaired parent in the pediatric office can be found in another clinical report from the American Academy of Pediatrics. 13 Indications of abuse or neglect would require a mandatory report to the child protective services agency.…”
Section: Methods To Assess and Engage The Family Affected By Parentalmentioning
confidence: 99%
See 1 more Smart Citation
“…Office staff could be encouraged to report any of these signs or symptoms to the pediatrician. 67 Additional guidance on dealing with the judgmentimpaired parent in the pediatric office can be found in another clinical report from the American Academy of Pediatrics. 13 Indications of abuse or neglect would require a mandatory report to the child protective services agency.…”
Section: Methods To Assess and Engage The Family Affected By Parentalmentioning
confidence: 99%
“…67 With supportive care, parents often are willing to enter drug treatment or engage in harm reduction on behalf of their children. Even when parents do not go to treatment, they may reduce use of the substances that they view as more threatening, such as methamphetamine, but increase marijuana or tobacco use.…”
Section: Methods To Assess and Engage The Family Affected By Parentalmentioning
confidence: 99%
“…Respondents with a total score of ≤1 point are at low AUD risk, respondents with a total score of 2 points are at moderate AUD risk, and respondents with a total score of ≥3 points are at high AUD risk (Dawson et al 2001). Shown to reliably identify AUD risk in other samples of young adult women (e.g., Cherpitel 1995;Fleming 2002;Russell et al 1996;Wilson et al 2008), the TWEAK displays "superior sensitivity and specificity" in relation to other well-known brief screeners, such as the CAGE and AUDIT (Flynn et al 2003:83;Russell et al 1996). For example, Cherpitel (1995) found that the TWEAK demonstrated sensitivity of 89% and specificity of 87% among female participants.…”
Section: Tweak Brief Screener For Alcohol Use Disordersmentioning
confidence: 99%
“…Previous studies in pediatric practices also found high maternal receptivity to health advice at well-child visits. 20,[28][29][30][31][32][33][34][35] This association suggests that well-child visits are an underused opportunity to address maternal risks for poor subsequent birth outcomes. The ICC approach we explored is consistent with recommendations by the American Academy of Pediatrics, which strongly advocates screening for maternal conditions such as smoking and depression at well-child visits.…”
mentioning
confidence: 99%